2012
DOI: 10.1096/fj.12-220509
|View full text |Cite
|
Sign up to set email alerts
|

C5L2: a controversial receptor of complement anaphylatoxin, C5a

Abstract: C5a is the paramount proinflammatory mediator of the complement cascade, and has been previously thought to act only through a single, G-protein-coupled, C5a receptor (C5aR; also termed CD88). In 2000, a second C5a receptor, C5L2 (previously known as GPR77), was discovered; yet, despite 12 yr of intensive research, its biological, or pathophysiological, function is both enigmatic and controversial. Unlike C5aR, this receptor does not couple to G proteins, and early studies promoted the hypothesis that C5L2 fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
163
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(168 citation statements)
references
References 57 publications
4
163
1
Order By: Relevance
“…In contrast, the expression levels of C5L2 are reduced in neutrophils from rats and humans with progressive sepsis, which is associated with poor prognosis [30]. Thus, the functional roles of C5L2 have still been controversial in sepsis [31]. Nevertheless, it is demonstrated that NKT cells minimally express C5L2 after E. coli infection, whereas these cells show high expression of C5aR [29].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the expression levels of C5L2 are reduced in neutrophils from rats and humans with progressive sepsis, which is associated with poor prognosis [30]. Thus, the functional roles of C5L2 have still been controversial in sepsis [31]. Nevertheless, it is demonstrated that NKT cells minimally express C5L2 after E. coli infection, whereas these cells show high expression of C5aR [29].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, C5aR and C5L2 are independent, and the putative 'default' receptor, C5L2, has an important role in balancing the biological effects of C5a. 6 However, the role of C5L2 in inflammatory responses is controversial, 7,8 its elucidation will require further investigation. In sepsis, it has been reported that excessive systemic C5a levels were associated with exhaustion of the granulocytic response.…”
Section: Introductionmentioning
confidence: 99%
“…After its generation, C3a is cleaved quickly at the C-terminal arginine to form C3a-desArg. This molecule has no detectable activity at C3aR, but it was shown by some groups to bind the second receptor for C5a, C5aR2 (C5L2) (17,18). The interactions with C5aR2 exhibit effects on metabolism and, in this sphere, C3a-desArg is homologous to acetylation-stimulating protein (19).…”
mentioning
confidence: 99%